Pembentukan dan Makna Kata Majemuk antara Onomatope dan Bagian Tubuh Manusia dalam Bahasa Jepang di Media Sosial Twitter - Pragasuri, Ni Nyoman Ayu Devi; Pradhana, Ngurah Indra; Budiana, I Made (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2020)
The title of this research is “Formation and Meaning of Compound Words from Onomatopoeia and Human Body Parts in Japanese on Social Media Twitter”. This research focuses on the forming process and meaning of compound words from onomatopoeia and human body parts in Japanese on social media twitter. This research was analysed by using formal and informal method. Compound words formation analysis used word formation theory from Kageyama and Kishimoto (2016) and the meaning of compound words analysis used semantic theory from Chaer (2012) and characteristic of Japanese onomatopoeia from Akimoto (2002). The result of this research is on the 25 data was analyzed, there are 14 data formed from the composition process and 11 data formed from the composition process followed by the shortening process of the words and part of speech classification in all data has changed. For the meaning, 22 data have grammatical meaning and 3 data have lexical meaning and all data have derivative meaning from the basic onomatopoeia.